Heavy Resistance Training in Hypoxia Enhances 1RM Squat Performance - Inness, Mathew W. H.; Billaut, François; Walker, Emily J.; Petersen, Aaron C.; Sweeting, Alice J.; Aughey, Robert J. (Frontiers in Physiology, 2016)
Purpose: To determine if heavy resistance training in hypoxia (IHRT) is more effective at improving strength, power and increasing lean mass than the same training in normoxia. Methods: A pair-matched, placebo-controlled study design included 20 resistance-trained participants assigned to IHRT (FIO2 0.143) or placebo (FIO2 0.20), (n=10 per group). Participants were matched for strength and training. Both groups performed 20 sessions over 7 weeks either with IHRT or placebo. All participants were tested for 1RM, 20-m sprint, body composition and countermovement jump pre-, mid- and post-training and compared via magnitude-based inferences. Presentation of Results: Groups were not clearly different for any test at baseline. Training improved both absolute (IHRT: 13.1 ± 3.9%, effect size (ES) 0.60, placebo 9.8 ± 4.7%, ES 0.31) and relative 1RM (IHRT: 13.4 ± 5.1%, ES 0.76, placebo 9.7 ± 5.3%, ES 0.48) at mid. Similarly, at post both groups increased absolute (IHRT: 20.7 ± 7.6%, ES 0.74, placebo 14.1 ± 6.0%, ES 0.58) and relative 1RM (IHRT: 21.6 ± 8.5%, ES 1.08, placebo 13.2 ± 6.4%, ES 0.78). Importantly, the change in IHRT was greater than placebo at mid for both absolute (4.4% greater change, 90% Confidence Interval (CI) 1.0:8.0%, ES 0.21, and relative strength (5.6% greater change, 90% CI 1.0:9.4%, ES 0.31 (relative)). There was also a greater change for IHRT at post for both absolute (7.0% greater change, 90% CI 1.3:13%, ES 0.33), and relative 1RM (9.2% greater change, 90% CI 1.6:14.9%, ES 0.49). Only IHRT increased countermovement jump peak power at Post (4.9%, ES 0.35), however the difference between IHRT and placebo was unclear (2.7%, 90% CI -2.0:7.6%, ES 0.20) with no clear differences in speed or body composition throughout. Conclusion: Heavy resistance training in hypoxia is more effective than placebo for improving absolute and relative strength.